2014
DOI: 10.3961/jpmph.2014.47.3.150
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sleep Duration on the Risk of Unintentional Injury in Korean Adults

Abstract: ObjectivesThe decrease or increase in sleep duration has recently been recognized as a risk factor for several diseases, including hypertension and obesity. Many studies have explored the relationship of decreased sleep durations and injuries, but few have examined the relationship between increased sleep duration and injury. The objective of this research is to identify the risk for injury associated with both decreased and increased sleep durations.MethodsData from the 2010 Community Health Survey were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
4
1
Order By: Relevance
“…In this study, those with 5 hours or less of sleep had 1.85-fold higher odds of injuries, and those with 6 hours of sleep had 1.45 higher odds more chance of injuries than those with approximately 9 hours of sleep (P < 0.05). Similar results were obtained by Kim 21 in his study, which investigated the relationship between hours of sleep and the likelihood of unintentional injuries. Similarly, sleep deprivation has been shown to lead to fatigue, drowsiness while driving, and impaired alertness, directly leading to an increased number of traffic accidents.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, those with 5 hours or less of sleep had 1.85-fold higher odds of injuries, and those with 6 hours of sleep had 1.45 higher odds more chance of injuries than those with approximately 9 hours of sleep (P < 0.05). Similar results were obtained by Kim 21 in his study, which investigated the relationship between hours of sleep and the likelihood of unintentional injuries. Similarly, sleep deprivation has been shown to lead to fatigue, drowsiness while driving, and impaired alertness, directly leading to an increased number of traffic accidents.…”
Section: Discussionsupporting
confidence: 87%
“…The use of medications also explains the increased rate of unintentional injuries among the elderly; for example, elderly individuals who consume opioid drugs are more likely to fall 20 . Furthermore, sleep duration affects unintentional injuries among adults; sleeping less than 6 hours was a risk factor for unintentional injuries 21 . The fall risk among elderly individuals is closely related to the activities of daily living (ADL) capability, physical activity habits, poor living conditions and environmental factors 22 .…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we found that the mean sleep duration of college students (8.2 h) was higher than that reported among adults in China (7.3 h) [24], United States (7.2 h) [25], and Korea (6.7 h) [26] or other college students from China (7.08 h) [17]. The proportion of students with sleep duration less than 7 h/day (6.3%) was lower than that reported in another study of Chinese college students (41.3%) [17].…”
Section: Discussioncontrasting
confidence: 62%
“…[29][30][31] In addition, Bhutan's average sleep time of 8.5 h is high when compared to other nationally representative studies from Finland (7.5 h), Austria (7 h), Korea (6.7 h), and United States (7.2 h). 19,[41][42][43] The high proportion of long sleepers in Bhutan could be because the majority of the respondents were from the rural areas without formal education. Furthermore, only 20% and 51% had access to internet and television, respectively, and 42% of the respondents were drinking alcohol.…”
Section: Discussionmentioning
confidence: 99%